Investigation of the Process of Simple Distillation in Irrigated Pipe Elements - Artem Sergeevich Ponikarov (MDPI AG, 2021)
In modern chemical and oil refining complexes, separation processes are among the most popular and energy-intensive. Installations for their implementation should be equipped with nodes for creating vapor (evaporators) and liquid (deflegmators) irrigation. Evaporators of any type (film, thermosiphon, gas lift, cubic) belong to this class of devices. For example, in cubic evaporators, the gas flow is completely formed from flux bubbles that originate on the heat-conducting surface and float in the volume of the cubic liquid located in the apparatus. Due to the accompanying mass exchange, the bubbles are enriched with volatile components during ascent and noticeably increase in volume, and the growth of the bubble is determined, among other things, by the total flow. At the same time, in real bubbling-type equipment, the total mass transfer surface exceeds the cross-section of the device itself by more than two orders of magnitude. Thus, according to, the ratio of the internal cross-sectional area of the apparatus to the developed mass transfer surface is 0.0015–0.002. Based on the analysis of the integral equation of the diffusion boundary layer, it is shown that the presence of a resultant flow of substance through the phase interface (non-equimolarity of the process) in a two-phase gas (vapor)–liquid system leads to the transformation of the structure of the traditional mass transfer equation itself. The use of a new structure obtained for both binary and multicomponent mixtures makes it possible to significantly simplify the approach to the description and generalization of arbitrary mass transfer processes. The innovativeness of the proposed approach lies in its universality for non-equimolar processes. This simplifies the creation of models of any mass transfer devices and entire production lines. In addition, the proposed approach is a good auxiliary tool for various researchers and experimenters. It should also be noted that the separation processes of many products of organic origin during heating are characterized by the appearance of undesirable side reactions (thermal decomposition, condensation, polycondensation, formation of harmful impurities, etc.), which occur most intensively in the heating zones. At the same time, the evaporation and distillation units are subject to requirements for the minimum hydraulic resistance of the structure, the maximum separation capacity (efficiency), and the minimum residence time of the product in the apparatus (equivalent to the minimum holding capacity of the structure). It was noted that the specified requirements are most fully met by film-type devices.